Writing a Blog Script to Promote Pinang Banjar Tourism in Gelumbang, South Sumatra - Jovanka Aurelya Catherin N. (Politeknik Negeri Sriwijaya, 2025)
This study discusses the development of a blog script to promote Pinang Banjar Tourism in Gelumbang, South Sumatra. The writer employed the Research and Development (R&D) method, as described by Sukmadinata (2017), which consists of three stages: Preliminary Study, Model Development, and Final Product Testing. Data were collected through literature studies, field observations, interviews, and documentation. The script was written using the AIDA model (Attention, Interest, Desire, Action) and enhanced with visual and structural elements, including a clear title, engaging content, and a call ot action. The final product is a blog titled “Pinang Banjar's Rural Natural Charm Presents a Beautiful and Peaceful Atmosphere” published on Blogger. It introduces Pinang Banjar as a tranquil, affordable, and scenic destination, offering activities such as boating and camping. Feedback from language experts, bloggers, and readers showed positive responses regarding both content and design. The blog effectively raises awareness of lesser-known tourism destinations and promotes sustainable tourism practices. Keywords: Blog Script, Pinang Banjar, Tourism Promotion, R&D, AIDA DOI: https://doi.org/10.5281/zenodo.18239388